Quantification of physiological disparities and task performance in stress and control conditions - Subhani, A.R. (2013)
In mental stress studies, cerebral activation and autonomic nervous system are important distinctly. This study aims to analyze disparities associated with scalp potential, which may have impact on autonomic activation of heart during mental stress. Ten healthy subjects participated in this study that performed arithmetic tasks in stress and control environment. Task difficulty was calculated from their correct responses. During the experiment, electroencephalogram (EEG) and electrocardiogram (ECG) signals were recorded concurrently. Sympathetic innervation of heart was estimated from heart rate (HR), which is extracted from the ECG. The value of theta Fz/alpha Pz was measured from EEG scalp potential. The results show a significant surge in the value of theta Fz/alpha Pz in stress as compared to baseline (p<0.013) and control (p<0.042). The results also present tachycardia while in stress as compared to baseline (p<0.05). Task difficulty in stress is also considerably higher than control environment (p<0.003). Â© 2013 IEEE.